Psicologia Sócio-Histórica na clínica: uma introdução - Silva, Maria Carolina Soares da (2019)
The main question this paper search to answer is oriented by paralyzed lives due to the organization of work environment when rigid form offers no way out for the mental flow (emotion), which then suffering is the number one consequence. Sociological & Historical Psychology in the Clinical practice brings in the historical-dialectical materialism methodology in order to listen better to the phenomenon that lies in between the person-social life relationship (specially, in this research, in the person-workplace organization relationship). The reason is important to validate the (mental) phenomenon generated in social life at the Clinical practice concerns the back seat it takes in the classical approach. The guideline of the paper is to show intricate patron of inter and intrasubjective relation when work impositions opposite to the emotional energy makes it impossible to see at workplace, but show up in another stance in life as suffering or “mysterious” disease apparently disconnected. It’s intended to discuss the following themes after theory revision: historical-dialectical materialism methodology; “activity” as a category; and the concept of workplace organization. The paper is structured into main two parts: the theory revision and the discussion presented to bring more ideas to Sociological & Historical Psychology at practice trough the use of scenes from one case study made for the purpose of this paper